Pharmacokinetic Team-Based Learning Experience: Phenytoin - Ann Snyder; Susan Markowsky; Erik Black; Justin De Leo (Association of American Medical Colleges, 2015)
Abstract This team-based learning exercise was designed to give participants a better understanding of phenytoin pharmacokinetics and healthcare system pitfalls through problem-solving during team discussions. Participants will learn to prioritize shortcomings in healthcare delivery and discuss approaches to improve health care quality while developing an appreciation for the complexity and application of phenytoin pharmacokinetics, dosage, and administration. In this case, multiple seizures occur in a patient who was initially stable on phenytoin dosage prior to hospitalization. The case facilitates discussion of oral phenytoin loading dosing, which helps beginning learners start to think about what software programs in computerized physician order entry (CPOE) can help to prevent medication errors. This work uses a student team and content evaluation to assess these learning outcomes. With the emphasis on competency-based programs and collaboration as a team, we used a team-based learning method model with 680 students from six different health disciplines continuous for the past 3 years. For this reason, we used the teamwork evaluation questions that have validated to assess perceptions of how they functioned as a team.